Urban fulfillment centers - Perceptions and expectations from retailers - Marike Kellermayr-Scheucher; Maria Niedermeier; Patrick Brandtner; Oliver Schauer (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Delivering goods to consumers and stores in dense urban environments is a challenging endeavor. Rising expectations in terms of speed, flexibility and choice of delivery further increase the intricacy of urban deliveries. This paper provides insights into how European retailers think about urban fulfillment centers (UFCs) in the context of Omnichannel retailing. Methodology: Based on a literature review, a questionnaire was developed for the empirical survey (semi-structured interviews) with twelve European retailers from different trade sectors. To analyze the interviews, MAXQDA and MS EXCEL were used. Interviews were also conducted with European logistics service providers as market experts and potential operators of UFCs. Findings: The results of the study reflect the different perceptions of UFCs among retailers. The extent to which UFCs are expected to play a role in future retail varies across interview partners: while some stated a positive impact and a high relevance of this concept in the near future, others expect no significant impact of UFCs and are not planning to invest into this concept in the next few years. Originality: The present results show an overview of the expectations and perceptions of European retailers regarding UFCs. To our knowledge, this is the first empirical survey to address this topic.
urn:nbn:de:gbv:830-882.0162177; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; City Logistics